Answer:
![\textsf{A.} \quad -2x + y = -2](https://img.qammunity.org/2023/formulas/mathematics/high-school/bqkx1y42jxj474urv3ya9cv34t83mj2477.png)
Explanation:
![\boxed{\begin{minipage}{5.5 cm}\underline{Standard form of a linear equation}\\\\$Ax+By=C$\\\\where:\\ \phantom{ww}$\bullet$ $A, B$ and $C$ are constants. \\ \phantom{ww}$\bullet$ $A$ must be positive.\\\end{minipage}}](https://img.qammunity.org/2023/formulas/mathematics/college/lih5oviws7ea942u2zyxwk0u7zl6jvozq2.png)
Given equation:
![y + 4 = 2(x + 1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/6fhrwf0efghq5przjxeh4aqmokt7in0ybs.png)
Distribute the right side of the equation:
![\implies y+4=2x+2](https://img.qammunity.org/2023/formulas/mathematics/high-school/mfvcn3vxcnaz5dnfby7vcrfi8y9l5wk5hb.png)
Subtract 2 from both sides:
![\implies y+4-2=2x+2-2](https://img.qammunity.org/2023/formulas/mathematics/high-school/6d97r7w8165h944cqoutotaar0xvgry1ua.png)
![\implies y+2=2x](https://img.qammunity.org/2023/formulas/mathematics/high-school/i1tllqgsak5un9zhmh57ab0ysalphkpf97.png)
Subtract y from both sides:
![\implies y+2-y=2x-y](https://img.qammunity.org/2023/formulas/mathematics/high-school/cuzp6iur8bfszjas0nh97zkeqo2plidldq.png)
![\implies 2=2x-y](https://img.qammunity.org/2023/formulas/mathematics/high-school/kk1us1ntepokr25d5ddmxdr44m5o0iiawz.png)
Switch sides:
![\implies 2x-y=2](https://img.qammunity.org/2023/formulas/mathematics/high-school/e9x3mc3ayp7xfqk55304s4n9uldi3rkkz6.png)
Therefore, the equation of the line written in standard form is:
![\boxed{2x-y=2}](https://img.qammunity.org/2023/formulas/mathematics/high-school/sjineejkzfhc4w5grczh8w9bkiwl34wzpv.png)
Since this is not one of the answer options, switch the signs:
![\implies -2x+y=-2](https://img.qammunity.org/2023/formulas/mathematics/high-school/t6yi38vvaz20dyepnsrmlfvqmf3dm2qa01.png)
Please note that this is not in standard form, since the coefficient of the term in x is negative. However, as the equation in strict standard form is not a given answer option, the only answer can be -2 + y = -2.